2001
DOI: 10.1007/bf02360282
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the physiological vigour of new potato cultivars in Switzerland

Abstract: SummaryDormancy, incubation periods and physiological vigour or rusticity of new potato cultivars were determined during the official cultivar assessment programme in Switzerland. A total of 60 cultivars were assessed, including the standards, Sirtema (early), Bintje (mid-early) and Eba (mid-late); Russet Burbank was re-examined. Large variation between cultivars was observed, from 2000 to 3400 day-degrees for dormancy and from 1900 to 3700 day-degrees for incubation periods, expressed as sums of cumulated tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
(1 reference statement)
0
7
0
1
Order By: Relevance
“…The method for describing physiological ageing must be simple, easy to use, precise, accurate and have predictive value. The use of thermal time as the basis of an ageing clock as it pertains separately to seed tubers and the developing sprouts (MacKerron, 1998) has potential practical use in comparative evaluations of cultivars (Reust, 1998) although there are serious limitations as noted previously.…”
Section: Future Directionsmentioning
confidence: 99%
“…The method for describing physiological ageing must be simple, easy to use, precise, accurate and have predictive value. The use of thermal time as the basis of an ageing clock as it pertains separately to seed tubers and the developing sprouts (MacKerron, 1998) has potential practical use in comparative evaluations of cultivars (Reust, 1998) although there are serious limitations as noted previously.…”
Section: Future Directionsmentioning
confidence: 99%
“…Knowles and Botar (1991) reported that ageinduced changes in sprouting can also be used to reasonably predict both yield level and quality. Early yields can also help reduce exposure of the potato crop to adverse weather, pests and other hazards that may limit yield and ⁄ or lower the quality of tubers (Horton 1987, Reust et al 2001). In addition, harvesting potatoes early can make the land available for other crops in a rotation.…”
Section: Introductionmentioning
confidence: 99%
“…However, no correlation (r = 0.01) was observed between parental tuber dormancy and SVI. So, the relationship between offspring TPS dormancy and their parent's tuber dormancy is unpredictable [22][23][24].…”
Section: Discussionmentioning
confidence: 99%